Age of the Ocean Floor: A Digital Data Set for the Labrador Sea and Western North Atlantic - Roest, Walter; Muller, R.; Verhoef, Jacob (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1992)
Abstract A digital grid of ocean floor ages was constructed from a combination of magnetic anomaly identifications and recent platekinematic models of the North Atlantic and Labrador Sea. Comparing large gridded geophysical data sets with these gridded agevalues is a powerful means of studying the variation of geophysical parameters with lithospheric age, and the dynamic processesin the Earth. The data set from the western North Atlantic and Labrador Sea shows the dependence on age of bathymetry, depth-to-basement and gravity.